Association of Diabetes Self-Care Management with Glycemic Control among Adults with Type 2 Diabetes in Bangladesh (Bangladesh Medical Journal, 2026)
Effective self-care is essential for achieving glycemic control, yet adherence remains suboptimal in many low- and middle-income settings, making an understanding of self-management patterns crucial for guiding patient-centered interventions. This study evaluates self-care practices and their relationship with glycemic outcomes among adults with type 2 diabetes mellitus (T2DM) attending tertiary hospitals in Bangladesh. A cross-sectional study of 278 adults with T2DM was conducted at two tertiary hospitals in Dhaka. Data were collected using a structured questionnaire covering socio-demographic characteristics, diabetes history, comorbidities, glycemic records, and the Diabetes Self-Management Questionnaire (DSMQ). Glycemic control was assessed using fasting blood sugar (FBS), 2-hour after breakfast glucose (2-HABF), and glycated hemoglobin (HbA1c). Descriptive statistics, chi-square tests, and Pearson’s correlation coefficients were used, with significance set at p